India Office Records ([S.l.] : India Office Library and Records, 1985)
The India Office Records are a very large collection of documents relating to the administration of India from 1600 to 1947, the period spanning Company and British rule in India.
Keywords: East India Company -- Records and correspondence; India -- History; India -- Politics and government